First ionospheric monitoring campaign at Fraser's Hill Malaysia - Zain, A.F.M; Ho, Yih Hwa; Abdullah, S; Abdullah, M (2006)
The ionosphere over Malaysia is unique because of her location near the equator where the existence of the equatorial anomaly, electrojet, and fountain effect have made it good for studies. As part of a rejuvenation process in investigating the equatorial ionosphere in Malaysia, a short duration ionospheric experimental campaign was carried out at Fraser's Hill (lat. 3° 42.9' N, long. 101° 44.2' E, at an altitude of 1298 m) from August 1 to 18, 2005. Two sets of equipment were installed; a digital ionosonde and a dual frequency GPS receiver. The ionosonde consists of the sounding equipment using a delta antenna for transmitting and a dipole antenna for receiving. The GPS dual frequency receiver that is co-located with the digisonde is utilized as an ionospheric scintillation and TEC monitor. Results are compared with the main observatory at Parit Raja (lat. 1° 86' N, long. 103° 8' E) Malaysia.